(untitled) (SAARC Journal of Agriculture, 2014)
An experiment was carried out during 2009-2010 on one hundred tamarind genotypes of the Nallur tamarind grove, a few kilometres away from Bengaluru International Airport, to investigate the genetic variability, character association and their direct and indirect effects on the fruit weight of tamarind. The genotypic coefficient of variation was high for seed weight, fibre weight, seed number, beak length and fruit weight. In all cases, phenotypic variances were higher than the genotypic variance. Moderate to high heritability as well as genetic advances were estimated for pod length, pod width, seed weight, seed number, number of ridges, number of furrows, pulp weight and fruit weight indicated that these traits was under additive gene control and selection for genetic improvement for these traits would be effective. Correlation studies revealed the highest significant association of fruit weight with seed weight followed by pulp weight, epicarp weight and seed number at genotypic and phenotypic level. Positive direct effects were produced by pulp weight and seed weight, while number of ridges had negative direct effects. The information obtained from the current studies can be used as selection criteria for genetic improvement of tamarind genotypes under study. DOI: http://dx.doi.org/10.3329/sja.v12i1.21109 SAARC J. Agri., 12(1): 20-25 (2014)